REVIEW ARTIKEL: PEMBUATAN DAN KARAKTERISASI MEMBRAN SELEKTIF ION TIPE KAWAT TERLAPIS - Cahaya, Tentriati; Panggabean, Aman Sentosa; Arif, Moh. Syaiful (PROSIDING SEMINAR KIMIA, 2025)
Industry in Indonesia is growing rapidly, causing an increase in waste including heavy metals and dyes that pollute waters. A method that can be used to detect these contaminants is the Coated Wire Type Ion Selective Electrode (ISE). ISE is an electrochemical sensor that is sensitive to ion activity, characterized by reversible potential changes. This method has the advantages of low cost, simple tools, and high selectivity. This study aims to compare membrane compositions to obtain optimal analytical results and examine electrode characteristics such as the price of the Nernst factor, linear concentration range, detection limit, response time, and life time. The results showed that variations in membrane composition affected electrode sensitivity and stability. This research is important for developing more efficient ISE for detecting heavy metals and dyes in polluted environments. Keywords : Ion Selective Electrode, Wire Coated, Potentiometry